2022
DOI: 10.1007/s11242-022-01782-8
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Distribution of Precipitates and Mineral Phase Transition During Biomineralization Affect Porosity–Permeability Relationships

Abstract: Enzymatically induced calcium carbonate precipitation is a promising geotechnique with the potential, for example, to seal leakage pathways in the subsurface or to stabilize soils. Precipitation of calcium carbonate in a porous medium reduces the porosity and, consequently, the permeability. With pseudo-2D microfluidic experiments, including pressure monitoring and, for visualization, optical microscopy and X-ray computed tomography, pore-space alterations were reliably related to corresponding hydraulic respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 59 publications
0
22
0
Order By: Relevance
“…Assuming a spherical shape of the crystals 30 , 37 , their equivalent diameter D was defined as the average of their minor and major axes (single or aggregate); thus, their equivalent volume is . The total mass of precipitated CaCO 3 at each sampled position was calculated: where ρ = 2.71 g/cm 3 is the density of calcite and n is the number of detected minerals (which can be both single crystals and crystal aggregates).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Assuming a spherical shape of the crystals 30 , 37 , their equivalent diameter D was defined as the average of their minor and major axes (single or aggregate); thus, their equivalent volume is . The total mass of precipitated CaCO 3 at each sampled position was calculated: where ρ = 2.71 g/cm 3 is the density of calcite and n is the number of detected minerals (which can be both single crystals and crystal aggregates).…”
Section: Methodsmentioning
confidence: 99%
“…Estimation of the chemical reaction efficiency of MICP. Assuming a spherical shape of the crystals 30,37 , their equivalent diameter D was defined as the average of their minor and major axes (single or aggregate); thus, their equivalent volume is…”
Section: Quantification Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…We investigate for the following use case a domain in which a chemically induced precipitation process clogs the pore space over time. Experimental data that are available online [16] is used and acquisition and experimental setup is described in [15].…”
Section: Application To Clogging Porous Materialsmentioning
confidence: 99%
“…Essentially, mineral nucleation is a critical factor in controlling the distribution of minerals over time and space. ,, The interplay between solute transport, nucleation, growth, and porous media structure is intricate. Several experimental and numerical studies have shown that the same amount of porosity reduction due to mineral precipitation might result in different permeability reductions. ,, ,,,, Furthermore, arbitrary selection of clogging models in RTMs may lead to considerable errors in predicted permeability for the same amount of porosity loss. , Despite all the mentioned variations and uncertainties, the permeability–porosity evolution during RTM in the continuum scale is usually oversimplified and handled with a single equation with a constant variable. Therefore, a process-based approach is necessary when analyzing permeability–porosity evolution.…”
Section: Introductionmentioning
confidence: 99%